KAJIAN RENCANA STRATEGIS BKAD KABUPATEN BANDUNG 2025-2029 - Kurniawan, Sandy (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2025)
This study examines the preparation of the Strategic Plan (Renstra) of the Regional Finance and Asset Agency (BKAD) of Bandung Regency for 2025–2029 as a key instrument in managing regional finances and assets. The main issues identified are the suboptimal operation of financial and asset management systems, and the limited utilization and legalization of assets as new revenue sources. The research aims to analyze the alignment of BKAD’s Strategic Plan with the 2025–2029 Regional Medium-Term Development Plan (RPJMD), regional vision and mission, and national policies, as well as to formulate performance improvement strategies. A descriptive qualitative method was applied through document review and SWOT analysis. The findings reveal that BKAD’s strengths include consistent Unqualified Opinion (WTP) achievement, functional human resources, and IT infrastructure, while weaknesses involve manual system integration and outdated asset data. Opportunities arise from national regulations and digitalization, whereas threats include rapid regulatory changes, HR competency gaps, and cybersecurity risks. The discussion highlights the urgency of accelerating asset certification, integrating systems, enhancing HR capacity, and strengthening cybersecurity to achieve transparent and accountable regional financial governance.